Psychometric analysis of the social connectedness instrument - Kelley, Brian; Fraser, Blake; Wells, Anessa; Ferdock, Matthew (Frontiers in Psychology, 2025)
IntroductionSocial connectedness is decreasing, especially among young adults, which poses a significant public mental and physical health threat globally. However, before attempting to improve social connectedness, measurement must first be evaluated. Many previous instruments used to measure loneliness (perceived social disconnectedness) provide a simple measure of intensity (i.e., how lonely/disconnected someone feels) but lack information about specific factors of loneliness and disconnectedness that are potentially modifiable (e.g., social skills, negative thoughts, technology use).MethodsThe current study aims to address these gaps by evaluating the psychometric properties of the Social Connectedness Instrument (SCI) using a sample of 719 college students (Mage = 19.63, SDage = 1.60, 75% female) attending a mid-Atlantic university. Psychometric evaluation, including exploratory factor analysis, principal component analysis, structural equation modeling, and tests of reliability and validity, was performed on the SCI.ResultsThe final model of the SCI consists of two latent constructs, Psychoemotional Disconnectedness (PED) and Psychosocial Disconnectedness (PSD), which displayed satisfactory psychometric properties overall. While PED refers to a perception of feeling disconnected due to emotional contributors (e.g., social anxiety, fear of rejection), PSD refers to a perception of feeling disconnected due to social contributors (e.g., social skills, social motivation). An additional eleven single-item indicators of disconnectedness, which were not included in the final model, may be retained for further insight into someone's disconnectedness if brevity is not an issue.DiscussionThis novel instrument is recommended for use when a greater depth of perceived social disconnectedness and potentially modifiable contributors are needed to inform individualized interventions.